Politically correct tourism discourse in airport websites guidelines for inclusive travelling - Elena Pasquini (Scripta Manent)
This work attempts to investigate inclusive discursive practices on the official websites of two European airports –namely Gatwick Airport and Orio al Serio International Airport – in order to explore how political correctness (PC), i.e. a contemporary sociolinguistic phenomenon pointing at transparency and inclusiveness in texts addressing disadvantaged categories, may influence tourism discourse. Chiefly, the analysis concerns online guidelines illustrating facilities for passengers with ‘special needs’, so as to shed light on whether and how undiscriminating language is employed to convey in the most neutral, accessible and thus persuasive way information to and about customers with ‘specific requirements’ within the realm of tourist communication. On this basis, the present study will be especially useful for pedagogical purposes, for professionals and students approaching the domain of tourism discourse and its discursive practices.